Polypropylene composite material as well as preparation method and application thereof

By adding high-density polyethylene resin, scratch-resistant additives and characteristic polar talc powder to the polypropylene resin, a polypropylene composite material is prepared, which solves the problems of low surface hardness and poor adhesive properties of polypropylene materials. It achieves high scratch resistance, strong bonding and high pulling rate, and is suitable for high-performance automotive parts.

CN119463353APending Publication Date: 2025-02-18TIANJIN KINGFA NEW MATERIAL +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411528185.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Simple polypropylene materials have low surface hardness and are easily scratched by sharp objects. In situations where it is necessary to bond to the flexible skin, it is difficult for the material to take into account both scratch resistance and adhesive properties.

Method used

A polypropylene composite material was prepared by adding high-density polyethylene resin and scratch-resistant additives to the polypropylene resin, and using characteristic polar talc powder and elastomer. The material is prepared through a twin screw extrusion mechanism, combining specific group distribution ratios and process parameters to improve the surface hardness of the material, bonding force with glue and drawing rate.

Benefits of technology

It significantly improves the surface hardness and scratch resistance of polypropylene composite materials, while enhancing the bonding force with glue, meeting the dual performance requirements in the leather and covering areas, and improving the drawing rate of the material. In applications of high-speed blasting or collision.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The polypropylene composite material comprises the following components in parts by weight: 58-91 parts of polypropylene resin; 5.5 to 13 parts of a compound scratch resistant agent; 5-10 parts of linear low density polyethylene; 5-10 parts of an elastomer; 10 to 23 parts of compound talcum powder; the compound scratch-resistant agent is a compound of high-density polyethylene and a scratch-resistant auxiliary agent in a weight ratio of (3-10): 1; the compound talcum powder is a compound of non-polar talcum powder and polar talcum powder in a weight ratio of (1-7): 1. The polypropylene composite material disclosed by the invention has the advantages of high surface hardness, strong binding force with glue and high drawing rate, and is suitable for workpieces with high-speed blasting and collision requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polypropylene composite material and a preparation method and application thereof. Background Art

[0002] Polypropylene has many advantages such as light density, high industrialization, wide variety and low cost, and is widely used in automotive interior and exterior decoration and functional parts. However, pure polypropylene material has disadvantages such as low surface hardness, easy to be scratched by sharp objects, and high gloss. In order to solve the above problems, high-end car models are currently coated on the surface of parts made of polypropylene. However, polypropylene material is a non-polar material. Generally, flame treatment or plasma process is used to activate the surface of polypropylene parts, and then polyurethane glue is used to bond soft surfaces such as PVC or TPV to polypropylene.

[0003] In order to further improve production efficiency, the current design trend is to have both a leather grain area and a coating area on the same part, where the leather grain area has a higher scratch resistance to polypropylene materials, while the non-leather grain area needs to be bonded to flexible surfaces such as PVC or TPV. This requires the material to have both scratch resistance and good bonding performance. At the same time, polypropylene materials that involve blasting or high-speed collisions also have higher impact performance and drawing rate, thereby improving the ability of the part to resist external damage. Summary of the invention

[0004] The object of the present invention is to provide a polypropylene composite material with high surface hardness, strong bonding force with glue and high drawing rate, and a preparation method and application thereof.

[0005] The present invention is achieved through the following technical solutions: A polypropylene composite material, comprising the following components in parts by weight: Polypropylene resin 58-91 parts; Compound scratch resistance agent 5.5-13 parts; 5-10 parts of linear low density polyethylene; Elastomer 5-10 parts; Compound talcum powder 10-23 parts; The compound scratch-resistant agent is a compound of high-density polyethylene and scratch-resistant additive, with a weight ratio of (3-10):1; The compound talcum powder is a compound of non-polar talcum powder and polar talcum powder, with a weight ratio of (1-7):1.

[0006] Preferably, the compounding ratio of high-density polyethylene to scratch-resistant additive in the compound scratch-resistant agent is (5-8):1.

[0007] The polar talc powder is surface-modified talc powder, and the surface contains at least one polar group of hydroxyl group and amino group.

[0008] Polar talc refers to talc with its surface modified by polar groups such as carboxyl and amino groups. Its preparation method may be, for example, adding substances containing carboxyl and amino groups during the processing of talc so that the surface of talc contains polar groups such as carboxyl and amino groups.

[0009] Non-polar talc is talc that has not been surface modified.

[0010] The particle size of the non-polar talcum powder is 1250-5000 meshes.

[0011] The particle size of the polar talcum powder is 1250-3000 meshes.

[0012] The polypropylene resin is selected from homopolymer polypropylene and / or copolymer polypropylene, with a melt index of 10-50 g / 10 min and a test condition of 230° C. / 2.16 kg. In the polypropylene composite material of the present invention, the polypropylene resin accounts for no less than 45 wt% of the total weight.

[0013] The scratch-resistant additive is at least one of polysiloxane, erucic acid amide and oleic acid amide; wherein the molecular weight of polysiloxane can be 800,000-1.5 million and can be added in the form of masterbatch.

[0014] The elastomer is selected from at least one of ethylene-octene copolymer, ethylene-propylene copolymer and ethylene-butene copolymer.

[0015] The high-density polyethylene has a melt index of 0.5-20 g / 10 min, and the test conditions are 190° C. / 2.16 kg.

[0016] The melt index of the linear low-density polyethylene is 0.9-10 g / 10 min, and the test conditions are 190° C. / 2.16 kg.

[0017] The melt index of the elastomer is tested under the conditions of 0.5-5 g / 10 min, 190° C. / kg, and 2.16 kg.

[0018] The test standard for the above melt index is: ISO 1133-1:2022.

[0019] It is possible to choose whether to add 0-2 parts of auxiliary agent according to the actual situation; the auxiliary agent is selected from at least one of an antioxidant and a light stabilizer.

[0020] The preparation method of the polypropylene composite material of the present invention comprises the following components: according to the proportion, the components are uniformly mixed, and extruded and granulated by a twin-screw extruder to obtain the polypropylene composite material. The temperature of the screw is set to 75-85°C for the first zone, 185-195°C for the second zone, 185-195°C for the third zone, 185-195°C for the fourth zone, 185-195°C for the fifth zone, 185-195°C for the sixth zone, 185-195°C for the seventh zone, 185-195°C for the eighth zone, and 185-195°C for the ninth zone; the main engine speed is 400-500 rpm; and the aspect ratio of the twin-screw extruder is (44-48):1.

[0021] The polypropylene composite material of the present invention is used for preparing vehicle-mounted parts, such as instrument panels, door panels, pillars, seats and the like, which need to meet the requirements of high-speed explosion or collision.

[0022] The present invention also includes a vehicle-mounted component having both a leather grain area and a coating area, which is prepared from the above-mentioned polypropylene composite material. The present invention has the following beneficial effects: The present invention can significantly improve the surface hardness of the material by adding a specific content of high-density polyethylene resin and a scratch-resistant additive to the polypropylene resin, thereby improving the scratch resistance of the material and reducing the influence of the precipitation of the scratch-resistant additive on the bonding strength with the glue; at the same time, the added specific content of polar talcum powder can effectively improve the surface polarity of the polypropylene material, thereby improving the bonding strength between the material and the glue. The two simultaneously balance and take into account the dual requirements of scratch resistance and coating bonding strength. At the same time, the added low-density polyethylene can effectively improve the drawing rate of the material, so that the material is suitable for some parts with high-speed blasting and collision requirements. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0024] The sources of raw materials used in the present invention are as follows: Polypropylene: PP EP548RQ, China Petrochemical Corporation, melt flow rate at 230°C and 2.16 kg weight is 28 g / 10 min; High-density polyethylene: HDPE DMDA 8008, Lanzhou Petrochemical, melt flow rate at 190°C and 2.16 kg weight is 8 g / 10 min; Linear low-density polyethylene: LLDPE 7042 (Jilin), Jilin Petrochemical, melt flow rate at 190°C and 2.16 kg weight is 2 g / 10 min; Low-density polyethylene: LDPE 2426H, CNOOC Shell, melt flow rate at 190 °C, 2.16 kg weight is 2 g / 10 min; Ethylene-butene copolymer: POE 7467, Dow Chemical, melt flow rate at 190°C and 2.16 kg weight is 1 g / 10 min; Ethylene-propylene copolymer: Vistamaxx POP 6102, ExxonMobil, melt flow rate 1.4 g / 10 min at 190 °C and 2.16 kg weight; Ethylene-octene copolymer: POE 8842, Dow Chemical, melt flow rate at 190°C, 2.16 kg weight is 1 g / 10 min; Non-polar talcum powder: mesh size is 3000 mesh, TYT-777A, Guangzhou Tianyuan Chemical Co., Ltd.; Polar talcum powder A: TP118B, polar group is amino, mesh size is 3000 mesh, Liaoning Aihai Yimi Mining Co., Ltd.; Polar talc powder B: Homemade, commercially available silane coupling agent KH-550 (γ-aminopropyltriethoxysilane) was added to the above non-polar talc powder TYT-777A to make the surface of the talc powder have amino groups; Polysiloxane: HG-600S, molecular weight 1.2 million, polysiloxane content accounts for 55%, the actual content of pure polysiloxane calculated from the polysiloxane content in the table, Zhejiang Jiahua Fine Chemical Co., Ltd.; Erucic acid amide: commercially available; Oleamide: Commercially available; The preparation method of the polypropylene composite material of the embodiment and the comparative example is as follows: according to the ratio, the components are mixed uniformly, and the polypropylene composite material is obtained by extruding and granulating through a twin-screw extruder. The temperature of the screw is set to 80°C for the first zone, 190°C for the second zone, 190°C for the third zone, 190°C for the fourth zone, 190°C for the fifth zone, 190°C for the sixth zone, 190°C for the seventh zone, 190°C for the eighth zone, and 190°C for the ninth zone; the main engine speed is 450 rpm; and the aspect ratio of the twin-screw extruder is 48:1.

[0025] Various test methods: (1) Scratch resistance: The Volkswagen scratch resistance test method PV3952 is used. A scraper with a load of 10N and a diameter of 1mm is used to scratch a 40*40 grid on the surface of the workpiece. The change in L value before and after scratching is determined. The standard requires △L≤1.5.

[0026] (2) Peel test: After the sample is treated with three-dimensional treatment, it is compounded with TPV using polyurethane glue and left to cure at room temperature for 7 days. Then, the ASTM D1876 standard test is used. The peel force must be ≥50N or the TPV and glue layer must be damaged to be considered qualified.

[0027] (3) Drawing rate: The material adopts the test standard of ISO 527, using 1A spline, 50mm / min test speed, and the elongation at break ≥75% to meet the requirements of high-speed collision or high-speed explosion.

[0028] Table 1: Composition (parts by weight) and test results of polypropylene composite materials of Examples 1-6 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Polypropylene 70 59 90 75 75 75 High Density Polyethylene 4.71 6 11.14 8.57 7.5 8.33 Polysiloxane 0.79 1.43 2.5 1.67 Erucamide 1 Oleamide 1.86 Linear low density polyethylene 8 5 10 7 7 7 Ethylene-octene copolymer 5 8 8 8 Ethylene-propylene copolymer 7 Ethylene-butene copolymer 10 Non-polar talc 12 8 18.4 14.4 14.4 14.4 Polar Talc A 3 2 4.6 3.6 3.6 3.6 △L 1.27 1.32 1.04 0.90 1.03 0.91 Peel test, N 78 64 86 84 82 85 Elongation at break, % 88 94 108 97 95 96 Table 2: Component composition (parts by weight) and test results of polypropylene composite materials of Examples 7-13 Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Polypropylene 75 75 75 75 75 75 75 High Density Polyethylene 8.89 9.09 8.57 8.57 8.57 8.57 8.89 Polysiloxane 1.11 0.91 1.43 1.43 1.43 1.43 1.11 Linear low density polyethylene 7 7 7 7 7 7 7 Ethylene-octene copolymer 8 8 8 8 8 8 8 Non-polar talc 14.4 14.4 9 13.5 15 15.75 14.4 Polar Talc A 3.6 3.6 9 4.5 3 2.25 Polar talc B 3.6 △L 0.94 1.04 0.96 0.92 0.93 0.96 0.99 Peel test, N 83 80 99 85 79 72 81 Elongation at break, % 99 102 96 97 95 96 97 It can be seen from Examples 4-8 that the preferred compounding ratio of high-density polyethylene: scratch-resistant additive has better scratch resistance and a better combination of peel strength and elongation at break.

[0029] Table 3: Component composition (parts by weight) and test results of polypropylene composite materials of comparative examples 1-5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Polypropylene 75 75 75 75 75 High Density Polyethylene 8.57 10 6.67 8.57 8.57 Polysiloxane 1.43 0 3.33 1.43 1.43 Linear low density polyethylene 7 7 0 2 Low density polyethylene 7 Ethylene-octene copolymer 8 8 8 8 8 Non-polar talc 14.4 14.4 14.4 14.4 14.4 Polar Talc A 3.6 3.6 3.6 3.6 3.6 △L 0.59 4.52 0.43 1.82 1.67 Peel test, N 72 64 43 47 49 Elongation at break, % 67 88 78 55 64 It can be seen from Comparative Example 1 that low-density polyethylene cannot replace linear low-density polyethylene.

[0030] It can be seen from Comparative Example 2 that all properties are poor if the scratch resistance additive is not contained.

[0031] It can be seen from Comparative Example 3 that if the ratio of high-density polyethylene to scratch-resistant additive is too low, the peeling force is poor.

[0032] It can be seen from Comparative Examples 4 / 5 that if the linear low-density polyethylene is not contained or the content is insufficient, all properties are poor.

[0033] Table 4: Component composition (parts by weight) and test results of polypropylene composite materials of Comparative Examples 6-7 Comparative Example 6 Comparative Example 7 Polypropylene 75 75 High Density Polyethylene 8.57 8.57 Polysiloxane 1.43 1.43 Linear low density polyethylene 15 7 Ethylene-octene copolymer 8 8 Non-polar talc 14.4 18 Polar Talc A 3.6 0 △L 0.55 0.58 Peel test, N 48 32 Elongation at break, % 79 56 It can be seen from Comparative Example 6 that when the linear low-density polyethylene content is too high, the peeling performance and elongation at break are poor.

[0034] It can be seen from Comparative Example 7 that if polar talc is not contained, the peeling performance and elongation at break are poor.

Claims

1. A polypropylene composite material, characterized in that: By weight, it includes the following components: Polypropylene resin 58-91 parts; Compound scratch resistance agent 5.5-13 parts; 5-10 parts of linear low density polyethylene; Elastomer 5-10 parts; Compound talcum powder 10-23 parts; The compound scratch-resistant agent is a compound of high-density polyethylene and scratch-resistant additive, with a weight ratio of (3-10):1; The compound talcum powder is a compound of non-polar talcum powder and polar talcum powder, and the weight ratio is (1-7):

1.

2. The polypropylene composite material according to claim 1, characterized in that: The compounding ratio of high density polyethylene in the compound scratch resistant agent: scratch resistant additive is (5-8):

1.

3. The polypropylene composite material according to claim 1, characterized in that: The polar talc powder is surface-modified talc powder, and contains at least one polar group of carboxyl and amino on the surface.

4. The polypropylene composite material according to claim 1, characterized in that: The particle size of the non-polar talcum powder is 1250-5000 meshes.

5. The polypropylene composite material according to claim 1, characterized in that: The polypropylene resin is selected from homopolymer polypropylene and / or copolymer polypropylene, with a melt index of 10-50 g / 10 min, and the test conditions are 230°C / 2.16 kg; the melt index of the high-density polyethylene is 0.5-20 g / 10 min, and the test conditions are 190°C / 2.16 kg; the melt index of the linear low-density polyethylene is 0.9-10 g / 10 min, and the test conditions are 190°C / 2.16 kg.

6. The polypropylene composite material according to claim 1, characterized in that: The scratch-resistant additive is selected from at least one of polysiloxane, erucic acid amide and oleic acid amide; the elastomer is selected from at least one of ethylene-octene copolymer, ethylene-propylene copolymer and ethylene-butene copolymer.

7. The polypropylene composite material according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents; the auxiliary agents are selected from at least one of antioxidants and light stabilizers.

8. The method for preparing the polypropylene composite material according to any one of claims 1 to 7, characterized in that: The invention comprises the following components: the components are uniformly mixed according to a proportion, and extruded and granulated by a twin-screw extruder to obtain a polypropylene composite material.

9. Use of the polypropylene composite material according to any one of claims 1 to 7, characterized in that: Used to prepare vehicle-mounted parts.

10. A vehicle-mounted component having both a leather grain area and a covering area, characterized in that: The polypropylene composite material is prepared from any one of claims 1 to 7.

Citation Information

Patent Citations

  • Scratch-resistant polypropylene composite material and preparation method thereof

    CN109749249A

  • Talcum powder filled polypropylene composite material as well as preparation method and application thereof

    CN114410013A

  • High-temperature-scratch-resistant polypropylene composite material as well as preparation method and application thereof

    CN114685899A